Financial literacy and financial management practice on financial performance of small Businesses in Ho Municipality - Tefe, Benjamin Kwaku (University of Cape Coast, 2025)
Despite the significance and involvement of small businesses to the economy, several empirical studies indicate that smallest businesses fail to grow with some folding up within the first few years of their operation due to poor financial performance. The purpose of this study was assess the effect of financial literacy and financial management practice on financial performance. The study discussed the financial management practice theory, resource-based theory. The study adopted the descriptive statistics and correlation analysis in a quantitative approach. With the help simple random sampling technique, 300 small businesses in the Ho Municipality were included in the study and the research employed a questionnaire to elicit the required data for the study. The study employed frequency tables, structural equation modelling and correlation analysis to examine financial literacy and financial performance with the mediating role of financial management practice between small enterprises in Ho Municipality. The study found out that financial management practices mediate financial literacy and financial performance nexus. Also, financial literacy had a positive effect of financial performance and financial management practices. Based on the findings of the study, we can conclude that sampled small enterprises in the metropolis were performing well financially and financial management practices mediated financial literacy. Moreover, the study recommended that, policies should be directed ensuring that first, managers of small enterprises are trained to become financial literate. Again, regular studies should be conducted for small enterprises manager on how to undertake financial management practices
xv, 104p;, ill
Keywords: Financial Literacy Financial Performance Small Enterprises Ho Municipality Financial Management Practice